Comprehensive characterization of the WRKY gene family and their potential roles in regulation phenylphenalenone biosynthesis in Musella lasiocarpa - Huang, Long; Li, Pirui; Tian, Mei; Feng, Xu; Chen, Yu; Feng, Boya; Zhao, Wanli (Frontiers in Plant Science, 2025)
Phenylphenalenone is an important phytoalexin for banana plant protection, yet the mechanisms governing its biosynthesis and regulation remain unclear in plant. WRKY transcription factors play essential roles in modulating plant growth, development, and the biosynthesis of secondary metabolites. In this study, we identified 158 WRKY genes (MlWRKYs) from a phenylphenalenone-rich plant species Musella lasiocarpa. Phylogenetic analysis classified the MlWRKY genes into three distinct subfamilies: type I, type II, and type III. Chromosomal distribution revealed that the MlWRKY genes are clustered on nine respective chromosomes. Additionally, synteny analysis between M. lasiocarpa and Musa balbisiana uncovered highly conserved collinear regions. MIWRKY15, MIWRKY111, MIWRKY122 were identified as candidate genes for regulating PhPNs biosynthesis by integration of multi-omics approaches. We further investigated the expression pattern of MIWRKY15, MIWRKY111, MIWRKY122 genes, as well as their putative target genes MlOMT22 and MlOMT27, the known phenylphenalenone biosynthesis genes in various tissues, including leaves, stems, roots, and seeds. MlWRKY15 and MlOMT22 showed similar expression patterns across tissues. MlWRKY122 and MlOMT27 also displayed consistent expression patterns, suggesting MlWRKY122 may regulate MlOMT27. Additionally, MlWRKY111’s expression was inversely correlated with MlOMT27, indicating a potential negative regulation of MlOMT27 by MlWRKY111. This study provides valuable insights into the WRKY family in M. lasiocarpa and will serve as a useful genetic resource for elucidating the regulatory mechanisms of phenylphenalenone biosynthesis.